Stroke nurse-led intravenous thrombolytic therapy strategy for ischemic stroke based on timeline process: A quality improvement program from China - Baiyu Li; Zhufeng Zhang; Keye Li; Lingdie Zhao; Rong Niu (Elsevier, 2024)
Objective: Early thrombolytic therapy for ischemic stroke within the therapeutic window is associated with improved clinical outcomes. This study investigated whether optimizing intravenous thrombolytic (IVT) therapy strategies for stroke could reduce treatment delays. Methods: To reduce delays in IVT therapy for ischemic stroke, a series of quality improvement measures were implemented at a tertiary hospital in Hangzhou, Zhejiang Province, from June 2021 to August 2023, which included developing a timeline process management system, forming a nurse-led stroke process management team, providing homogeneous training, standardizing the IVT therapy process for ischemic stroke, and introducing an incentive policy. During the pre- (from June 2021 to February 2022, group A) and post- (from March to November 2022, group B1; from December 2022 to August 2023, group B2 [implementation of an additional incentive policy]) of the implementation the strategy, the door-to-computed tomographic angiography (CTA) time (DCT), CTA time, neurology consultation to consent for IVT, CTA-to-needle time (CNT), and door-to-needle time (DNT), the percentage of people who underwent CTA within 20 min, 15 min, and 10 min and DNT within 60 min, 45 min, and 30 min were collected and compared. Results: Following the implementation of the standardized IVT process management strategy for stroke, the DNT for group B1 and group B2 were 30 (24, 44) min and 31 (24, 41) min, respectively, both significantly lower than the 46 (38, 58) min in group A (P < 0.001); the median DCT were both 13 min in group B1 and B2 lower than 17min in group A (P < 0.001); the median CTA were 12 min in Group B1 and 9 min in Group B2 lower than 14 min in group A (P < 0.001); similar results were observed during the neurology consultation to obtain consent for IVT and CNT. Compared with group A, the proportion of DCT ≤ 20 min, 15 min, and 10 min was higher in groups B1 and B2 (P < 0.05), and the same result was observed at DNT ≤60 min, 45 min, and 30 min (P < 0.05). However, the additional incentive policy did not significantly differ between Group B2 and Group B1. Conclusions: Optimizing IVT therapy for ischemic stroke is a feasible approach to limit the DNT to 30 min in ischemic stroke, significantly reducing delays within the therapeutic window and increasing the number of patients meeting target time segments. Additionally, generating a timeline for the IVT therapy process by scanning positioning quick response codes was a significant breakthrough in achieving the informatization of IVT quality management for stroke.